Catalyzing Change: Unleashing the Power of Artificial Intelligence in Indonesian Business - Suraji, Robertus; Istianingsih; Ali, Hapzi (Green Publisher, 2024)
Artificial Intelligence (AI) has become a transformative force in the modern business world. This research analyzes the impact of AI adoption in businesses, focusing on the Indonesian business context. We combine literature analysis, cross-sector case studies, and interviews with business stakeholders. The research findings indicate that AI has shifted the business paradigm in Indonesia by enhancing operational efficiency, altering traditional business models, and supporting better decision-making. Challenges related to algorithmic bias and AI ethics are also identified. The implications of this research include the need for thoughtful management of AI adoption, collaboration with regulators, and increased education and awareness regarding social impact and ethics. Further research can deepen the understanding of AI's impact in diverse business contexts in Indonesia. This research provides a solid foundation for understanding AI's role in modern business, bridging the global and local dimensions to detail the impacts, challenges, and opportunities faced by organizations adopting this technology.